Context Dependent Games as Quantifiers and Selection Functions - Jules Hedges; Paulo Oliva; Evguenia Winschel; Viktor Winschel; Philipp Zahn (University of Mannheim, Department of Economics, 2014)
We use quantifiers and selection functions to represent simultaneous move games. Quantifiers and selection functions are examples of higher-order functions. A higher order function is a function whose domain is itself a set of functions. Thus, quantifiers and selection func- tions allow players to form goals not only about outcomes but about the whole (or parts) of the game play. They encompass standard pref- erences and utility functions as special cases, but also extend to non-maximizing behavior and context-dependent motives. We adapt the Nash equilibrium concept to our new representation and also introduce a refinement to capture the essential features of context-dependent motives. As an example, we discuss fixpoint operations as context dependent goals of coordination and differentiation in simultaneous game variants of Keyne's beauty contest and the minority game.
urn:nbn:de:bsz:180-madoc-361786
Keywords: C0; D01; D03; D63; D64; 330; context dependent refinement of Nash equilibrium; higher order functions; quantifiers; selection functions; beauty contest; minority game; endogenous economist